Post-operative Bleeding Risk in Dental Surgery for Patients on Oral Anticoagulant Therapy: A Meta-analysis of Observational Studies - Shi, Quan; Xu, Juan; Zhang, Tong; Zhang, Bin; Liu, Hongchen (Frontiers in Pharmacology, 2017)
Background and Objective: Minor dental surgery is invasive and hemorrhagic. Thus, in patients treated with anticoagulants, the bleeding risk related to these invasive procedures is concerning. The aim of this meta-analysis is to evaluate this risk by comparing the postoperative bleeding rates of oral anticoagulation treatment (OAT) patients (without interrupted or altered anticoagulant intake) with non-OAT patients. Methods: PubMed, Embase and the Cochrane Library were searched for eligible studies that compared the postoperative (following minor dental surgery) bleeding rates of OAT patients without interrupted or altered therapy with those of non-OAT patients. Relative risk (RR) and 95% confidence interval (CI) were calculated. Subgroup analyses were used to identify the association between the bleeding rate and different dental surgeries or anticoagulants. Results: 32 full text articles were assessed for eligibility and 20 studies were excluded according to the selection criteria. Finally, 12 studies and a total of 2102 OAT patients and 2271 non-OAT patients were included. A pooled analysis indicated that the postoperative bleeding risk in OAT patients is higher than that of non-OAT patients (RR: 2.794, 95% CI: 1.722-4.532, P=0.000). The pooled relative risks in the dental implant surgery and dental extraction subgroups were 2.136 (95% CI: 0.825-5.531, P=0.118) and 2.003 (95% CI: 0.987-4.063, P=0.054), respectively. As for the different oral anticoagulants, the pooled RR in the subgroup of new oral anticoagulants (NOACs) was 1.603 (95% CI: 0.430-5.980, P=0.482), while the pooled RR in the vitamin K antagonists subgroup was 3.067 (95% CI: 1.838-5.118, P=0.000). Conclusions: Under current evidence, OAT patients were under a higher postoperative bleeding risk than the non-OAT patients following minor dental surgery. For the dental implant surgeries and dental extractions, our study failed to demonstrate a higher risk of bleeding in the OAT patients compared with the non-OAT patients. Besides, The NOACs might be safer than the vitamin K antagonists in dental implant surgery. However, more well-designed studies are required for future research.